Kelana Agresif Automart (M) Sdn Bhd / Muhammad Zuhilmi Muhammad Zaidi - Muhammad Zaidi, Muhammad Zuhilmi (Faculty of Business and Management, 2023)
Industrial training is compulsory for each student at University Teknologi Mara (UiTM) in semester 6, which is a part of the academic credit hour to achieve a degree status. As a final year student, I am required to undergo an industrial training program at Kelana Agresif Automart (M) Sdn. Bhd, which is one of PERODUA franchises that provided services such as repairing, painting and insurance services. The industrial training program will take around 24 weeks, from 1 March 2023 until 15 August 2023. The main purpose of this industrial training is to complete the course in order to achieve the degree in Office System Management as well as graduated from university. Industrial training is important because it will teach, expose, and give an experience for students to know how the real working environment. Besides that, practical training can help the students to gain new knowledge through hands-on observation and job execution. I am undergoing this industrial training to seek input from my service manager and all staff. Every task and job that has been assigned in the training is also stated for the employment work-study.